Dye-Sensitized Solar Cells Prepared with Mexican Pre-Hispanic Dyes - Mario Alberto Sánchez-García; Xim Bokhimi; Sergio Velázquez Martínez; Antonio Esteban Jiménez-González (Journal of Nanotechnology)
A dye-sensitized solar cell (DSSC) is a photovoltaic device capable of generating electrical power from the absorption of solar radiation. These cells use a SnO2 : F/TiO2/dye heterojunction as the active electrode (working electrode). Active electrodes containing TiO2 in the anatase crystalline phase and synthetic dyes are used to achieve high conversion efficiencies. Synthetic dyes, whether organic or organometallic compounds, have the disadvantage of being expensive. For this reason, many efforts are made worldwide to find natural dyes with lower production costs that can be used in the fabrication of DSSCs. Nocheztli is a natural red dye obtained from the cochineal insect Dactylopius coccus; the dye dates from pre-Hispanic times and contains high levels of carminic acid (CA). Nocheztli has been used in Mexico in textile dyeing from pre-Hispanic times to the present. Carmine is an organometallic dye with two molecules of carminic acid and one atom of aluminum in its structure; it is obtained by the interaction of the carminic acid from Nocheztli with aluminum salts. Carminic acid and carmine molecules contain a carboxyl group in their structure, allowing them to anchor to TiO2, creating a suitable heterojunction to prepare DSSCs. In this study, both dyes are used to sensitize the mesoporous TiO2m semiconductor to prepare DSSCs.